Koreksi dimensi vertikal oklusal dengan modifikasi restorasi mahkota logam pada kasus severe early childhood caries (Correcting occlusal vertical dimension using modified stainless steel crown restoration in severe early childhood caries case) - Amrita Widyagarini; Sarworini B Budiardjo (Dental Journal (Majalah Kedokteran Gigi), 2014)
Background: Severe early childhood caries (SECC) describes progressively dental caries in primary dentition among children aged less than 3 to 5-year-old. Loss of Occlusal Vertical Dimension (OVD) with deep bite in clinical feature found 2.5 times more often in s-ecc children than others. It leads discrepancies of vertical development of permanent dentition, hence creates malocclusion. Purpose: The aim of this paper was to report consideration and correction of OVD in SECC child. Case: A 5-year-old girl was accompanied by her mother came to pediatric dental clinic Faculty of Dentistry Universitas Indonesia. Patient’s chief complaint was decay on all her teeth. Clinical examination revealed caries on all primary dentition, tooth #16, #46 have not yet been occluded, 26 erupted partially and it occluded with 36, anterior deep bite. Diagnose was anterior deep bite caused by SECC. Case management: Operative-rehabilitative treatment restores OVD to prevent malocclusion by modifying height of ssc in primary molars. Correcting deep bite using stainless steel crown (SSC) modified in posterior was done. First, restoration with glass-ionomer cement for raising the bite followed by a week evaluation to observe masticatory function and functional analysis of temporomandibular joint. Second, ssc were placed in primary molars. Conclusion: Modifying height of ssc in primary molars could corrected OVD in SECC child. Permanent first molars eruption could be guided to completely occlusion and prevent early malocclusion.Latar belakang: Severe early childhood caries (SECC) menunjukan pola karies gigi sulung yang progresif dan menyeluruh pada anak usia di bawah 3 hingga 5 tahun. Kehilangan dimensi vertikal oklusal (DVO), dengan gambaran gigitan dalam pada periode gigi sulung dilaporkan terjadi 2,5 kali lebih banyak pada anak SECC. Hal ini dapat menyebabkan gangguan perkembangan vertikal gigi permanen yang nantinya menyebabkan maloklusi. Tujuan: Laporan kasus ini melaporkan mengenai pertimbangan dan koreksi dimensi vertikal pada anak SECC. Kasus: Anak perempuan, 5 tahun, diantar ibunya ke klinik gigi anak Fakultas Kedokteran Gigi Universitas Indonesia dengan keluhan semua giginya karies. Klinis, seluruh gigi sulung karies, #16, #46 belum mencapai oklusi, #26 erupsi sebagian dan beroklusi dengan #36, gigitan dalam regio anterior. Diagnosis adalah gigitan dalam regio anterior karena SECC. Tatalaksana kasus: Perawatan operatif-rehabilitatif bertujuan mengembalikan DVO guna mencegah maloklusi, antara lain dengan memodifikasi restorasi mahkota logam gigi posterior. Dilakukan koreksi gigitan dalam regio anterior dengan modifikasi restorasi mahkota logam gigi posterior. Tahap pertama, restorasi glass-ionomer cement dengan meninggikan gigitan gigi posterior. Adaptasi gigitan selama 1 minggu dan pengamatan fungsi pengunyahan serta analisa fungsional temporomandibular joint. Kedua, restorasi mahkota logam gigi molar, dengan mempertahankan tinggi gigit tahap pertama, dilanjutkan restorasi mahkota untuk gigi anterior. Simpulan: Modifikasi tinggi restorasi mahkota logam seluruh gigi molar sulung kasus SECC, dapat mengembalikan DVO, sehingga erupsi empat gigi molar satu permanen dapat mencapai oklusi sempurna, dan mencegah maloklusi dini.